Direction: In the following questions, A statement of Assertion (A) is followed by a statement of Reason (R). Mark the correct choice as
Assertion (A) : If A = A_{1 }∪ A_{2}… ∪ A_{n}, where A_{1}… A_{n} are mutually exclusive events then
Reason (R) : Given, A = A_{1} ∪ A_{2} ... ∪ A_{n}
Since A_{1}...A_{n} are mutually exclusive P(A) = P(A_{1}) + P(A_{2})+ ….+P(A_{n})
Direction: In the following questions, A statement of Assertion (A) is followed by a statement of Reason (R). Mark the correct choice as
Assertion (A) : If A ⊂ B and B ⊂ A then, P(A) = P(B).
Reason (R) : If A ⊂ B then
1 Crore+ students have signed up on EduRev. Have you? Download the App 
Direction: In the following questions, A statement of Assertion (A) is followed by a statement of Reason (R). Mark the correct choice as
Assertion (A) : If A and B are two mutually exclusive events with = 5/6 and P(B) = 1/3. Then is equal to 1/4.
Reason (R) : If A and B are two events such that P(A) = 0.2, P(B) = 0.6 and P(AB) = 0.2 then the value of
Direction: In the following questions, A statement of Assertion (A) is followed by a statement of Reason (R). Mark the correct choice as
Assertion (A) : The probability of an impossible event is 1.
Reason (R) : If A is a perfect subset of B and P(A) < P(B), then P(B – A) is equal to P(B) – P(A).
Direction: In the following questions, A statement of Assertion (A) is followed by a statement of Reason (R). Mark the correct choice as
Assertion (A) : Let A and B be two events such that the occurrence of A implies occurrence of B, but not viceversa, then the correct relation between P(A) and P(B) is P(B) ≥ P(A).
Reason (R) : Here, according to the given statement P(B) = P(A ∪ (A ∩ B)
(∵ A ∩ B = A)
= P(A) + P(A ∩ B)
Therefore, P(B) ≥ P(A)
Direction: In the following questions, A statement of Assertion (A) is followed by a statement of Reason (R). Mark the correct choice as
Assertion (A): Let A and B be two events such that P(A) = 1/5 , while P(A or B) = 1/2. Let P(B) = P, then for P = 3/8 , A and B independent.
Reason (R) : For independent events, P(A ∩ B) = P(A) P(B)
P(A ∪ B) = P(A) + P(B) – P(A ∩ B)
= P(A) + P(B) – P(A) P(B)
⇒
⇒ P = 3/8.
204 videos288 docs139 tests

204 videos288 docs139 tests
